Tobin Tax: Reducing the negative effects of capital controls and short-term capital movements - Hülya Öztürk; Zeynep Karaçor; Perihan Hazel Er (Journal of Contemporary Economic and Business Issues, 2015)
The phenomenon liberalization, with the influence of the Bretton Woods system that collapsed subsequent to the Oil Shock in 1970, first began with the efforts to discover markets to value the investments of these countries in the developed countries. In order to provide the desired capital figures, in the 1980s the developed countries, squeezed under the debt load together with insufficient capital accumulation and low saving rates, needed the foreign resources and, at this point, the liberalization process of capital gained importance. Realizing the growth and developmental targets of countries' economies, their integration in the liberalization gained great importance. The developing countries' integration in the system without the necessary arrangement in their financial structures had an effect in terms of disturbing the stability of the economies, particularly in short-term capital inflows. As much as the problem created by the speculative capital inflow, the immediate outflow of this capital, disturbing the balance of economies, also caused crisis. To minimize the negative influence of short-term capital, capital controls are emphasized. Just as these controls can have various application ways, the most emphasized and discussed application was Tobin tax. Even though there are various disagreements in terms of whether or not Tobin tax affected the capital inflows, the examples of Malaysia and Chile represent successful results. In the first section of this study, the development of the liberalization process will be examined. In the second section, the effects created by the capital movements, and particularly short-term capital movements, on the countries' economies will be emphasized. In the third section, the capital controls and Tobin tax, suggested for reducing the negative effects of the short-term capital movements will be considered and the applicability and limitations of Tobin tax will be examined.
Keywords: G10; E66; F38; O40; J10; H29; 330; Liberalization; Capital control; Tobin tax; long termed capital movements